2009
DOI: 10.1007/s11244-009-9309-y
|View full text |Cite
|
Sign up to set email alerts
|

Linking Simultaneous In Situ WAXS/SAXS/Raman with Raman/ATR/UV–vis Spectroscopy: Comprehensive Insight into the Synthesis of Molybdate Catalyst Precursors

Abstract: A new setup is presented which enables simultaneous wide-and small-angle X-ray scattering (WAXS/SAXS) and Raman spectroscopic experiments during the synthesis of Mo-based mixed oxide catalyst precursors at the l-spot beamline at the Berliner Elektronenspeicherring-Gesellschaft für Synchrotronstrahlung (BESSY). Furthermore, we report about the separate monitoring of the same reactions under comparable conditions by simultaneous combined ATR/UV-vis/Raman spectroscopic measurements. For testing the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…[1] In recent years the analytical tools for in situ investigations of chemical reactions under real reaction conditions were significantly developed. [2][3][4][5][6][7][8][9][10][11][12][13] We and others demonstrated that a wealth of information is gained by applying in situ XRD, in-situ total scattering, or in-situ X-ray absorption spectroscopy during chemical reactions. [10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Despite the increasing efforts to gain insight into mechanisms of chemical reactions, in situ X-ray scattering studies under real reaction conditions are still rarely performed.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In recent years the analytical tools for in situ investigations of chemical reactions under real reaction conditions were significantly developed. [2][3][4][5][6][7][8][9][10][11][12][13] We and others demonstrated that a wealth of information is gained by applying in situ XRD, in-situ total scattering, or in-situ X-ray absorption spectroscopy during chemical reactions. [10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Despite the increasing efforts to gain insight into mechanisms of chemical reactions, in situ X-ray scattering studies under real reaction conditions are still rarely performed.…”
Section: Introductionmentioning
confidence: 99%
“…To probe the structural changes of catalysts under reaction conditions, in situ and, in particular, operando Raman spectroscopy are suitable tools . In the case of metal molybdates, it is possible to identify different molybdate structures by their characteristic spectroscopic features . Thus, we have demonstrated recently by operando Raman spectroscopy of mixed molybdate catalysts under propene oxidation conditions that the formation and changes of molybdate phases induced by exposure to different reaction gas mixtures can be followed by inspecting the intensity changes of their characteristic bands.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] In the case of metal molybdates,i t is possible to identify different molybdate structures by their characteristic spectroscopic features. [12][13][14][15][16][17][18][19] Thus,w ehave demonstrated recently by operando Raman spectroscopy of mixed molybdate catalysts under propene oxidation conditions [20] that the formation and changes of molybdate phases induced by exposure to different reactiong as mixtures can be followed by inspecting the intensity changes of their characteristic bands. In accordance with the above-mentioned in situ Mçssbauer experiments, [5] Inspiredb yt hese first optimistic results we extended our studies on the ammoxidation of propene to acrylonitrile over mixed molybdate catalysts ystems.…”
Section: Introductionmentioning
confidence: 99%
“…Following these pioneering works, the liquid‐phase synthesis of these and other advanced materials has been subjected to scrutiny. In a short, and by no means an exhaustive survey, we can highlight more recent examples dealing with zeolites/zeotypes19, 20 and oxides 21. 22, 23 XRD–XAS–SAXS (SAXS:small angle X‐ray scattering) and Raman or, in some cases, UV‐visible spectroscopy combination(s), is (are) the preferred option(s), owing to inherent limitations of other techniques, which cannot easily handle signals evolving in the aqueous or organic media required by the synthesis.…”
Section: Resultsmentioning
confidence: 99%